Aortic elastic properties predict occult coronary artery disease: a multidetector row computed tomography study - (:unkn) unknown (POLSKIE TOWARZYSTOWO KARDIOLOGICZNE, 2015)
Background: Multidetector row computed tomography ( MDCT) is an attractive noninvasive imaging modality to detect coronary atherosclerotic plaques which may be underestimated by conventional angiography. However, its routine clinical use is limited due to contrast-associated problems, high cost, inapplicability at bedside and exposure to radiation. Thus, exploring safer and more practical measurements to predict occult coronary artery disease (CAD) is required. Aim: To demonstrate the predictive value of aortic elastic properties for occult CAD diagnosed by MDCT. Methods: Forty subjects with angiographically normal coronary arteries were consecutively included in our study. They underwent MDCT including indications and were divided into a no CAD group (23 subjects, 11 males, 46 +/- 8 years) and an occult CAD group (17 subjects, 12 males, 48 +/- 10 years), with respect to the presence of coronary plaque. As a control group, 19 consecutive patients with angiographically proven CAD (16 males, 52 +/- 6 years) were included. Aortic stiffness index (ASI), aortic distensibility and aortic strain were calculated from the aortic diameters measured by echocardiography and blood pressure obtained by sphygmomanometry. Results: It was found that ASI, aortic distensibility and aortic strain were significantly different in the occult CAD group compared to the no CAD group (p = 0.008, p = 0.01, p = 0.03, respectively) and to the evident CAD group (p = 0.01, p = 0.02, p = 0.02). They also differed significantly between the no CAD and the evident CAD groups. Receiver operating characteristics analysis for ASI, to distinguish between the occult CAD group and the no CAD group, revealed an area under the curve of 0.80 (confidence interval 0.68-0.94, p = 0.004) and that the cut-off value of 3.42 could significantly predict patients with occult CAD (sensitivity: 78%; specificity: 63%). Conclusions: Measurement of ASI is an easily applicable and safe method with its non-radiographic ability for the assessment of aortic stiffness, and it may be useful to predict subclinical atherosclerosis in clinical practice. A cut-off value of 3.42 for ASI may guide to refer individuals to preventive strategies to reduce atherosclerosis progression.
Keywords: coronary artery disease; computed tomography; atherosclerosis; angiography; PULSE-WAVE VELOCITY; CARDIOVASCULAR MORTALITY; BLOOD-PRESSURE; STIFFNESS; DISTENSIBILITY; HYPERTENSION; ANGIOGRAPHY; THERAPY; MEN